Koneksi Politik Memoderasi Hubungan Struktur Dewan Direksi Dan Komisaris Terhadap Kualitas Laba Di Indonesia - Pamuji, Ba'ti Putri; Naimah, Zahroh (E-Jurnal Akuntansi; Vol 32 No 12 (2022), 2022)
This research was conducted to obtain empirical evidence testing the relationship between the structure of the board of directors and commissioners on the quality of company earnings and to test the moderating effect of political connections on the relationship between the two. The population and research sample used all companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2018 range with sampling determined by purposive sampling technique. The data analysis technique uses multiple regression techniques and Moderated Regression Analysis (MRA) to examine the moderating effect on political connection variables. The results of the analysis prove that the structure of the board of directors and commissioners has a positive effect on the quality of company earnings and political connections moderate the relationship between the two. This research provides practical implications for business people to pay attention to the structure of the board of directors and commissioners in corporate organizations as well as the issue of political connections in creating a good corporate climate. Keywords: Political Connection; Board Structure; Earnings Quality.